Wzrost konkurencyjności regionu świętokrzyskiego w aspekcie realizowanych programów wsparcia finansowanych z funduszy strukturalnych ze szczególnym uwzględnieniem regionalnej strategii innowacji - Braziewicz, Olga (The Increase of the Świętokrzyskie Region Competitiveness as a Result of the Implementation of Financial Aid Programs Obtained from Structural Funds with Particular Consideration of Regional Innovation Strategy, 2006)
The European Union has recently been one of the issues which are most often dealt with in all possible disciplines. The problems of regional politicy and the intensification of social and economical coherence of particular EU members by means of supporting the less developed regions offer us multiple discussion possibilities. In the article we would like to collect and systematize the topics mentioned above, giving it not only a general view but considering the problem from the perspective of one of the least developed regions which the Świętokrzyskie region undoubtedly is. Compared to other regions this region is characterized by low economical profitability, the flee of young, educated people and outdated research infrastructure. Regional Innovation Strategy is a quintessence of the opportunities of use and distribution of the EU financial aid regardless of its source. The implementation of Regional Innovation Strategy is meant to lead to the increase of the region's attractiveness as well as to increase its competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 183-192